Hyper IgE Syndrome in an Isolated Population in Israel - Lachover-Roth, Idit; Lagovsky, Irina; Shtorch-Asor, Atalia; Confino-Cohen, Ronit; Reinstein, Eyal; Garty, Ben-Zion (Frontiers in Immunology, 2022)
Introduction: Hyper IgE syndrome (HIES) is a group of rare primary immunodeficiency syndromes characterized by high levels of serum IgE, cold abscess, pulmonary infections, and eczema. ZNF341 deficiency was described in 2018 in 11 patients diagnosed previously with HIES but without a genetic diagnosis. Eight of those patients, all offspring of consanguineous couples, are from three families who live in a Muslim village in Israel which has approximately 15,000 residents. Objective: Our study aimed to evaluate the prevalence of ZNF341 mutation in the population of the village. Methods: Three hundred DNA samples of females who were referred for prenatal genetic testing before pregnancy, during 2017-2019, in Meir Medical center were included in the study: 200 samples were from the village, and 100 samples of Muslim females were from other villages. All samples were tested by Sanger sequencing for the ZNF341 mutation (c.904C>T, NM_001282933.1). Results: Heterozygous nonsense mutation in ZNF341 was found in 10 samples (5%) of the study group compared to zero in the control group (p<0.01). Conclusion: The carrier frequency of the mutation in ZNF341 in the village population is 1:20. This high frequency is probably due to founder mutation and consanguineous marriages.